2017
DOI: 10.1242/dmm.028530
|View full text |Cite
|
Sign up to set email alerts
|

Dietary reversal of neuropathy in a murine model of prediabetes and the metabolic syndrome

Abstract: Patients with metabolic syndrome, which is defined as obesity, dyslipidemia, hypertension and impaired glucose tolerance (IGT), can develop the same macro- and microvascular complications as patients with type 2 diabetes, including peripheral neuropathy. In type 2 diabetes, glycemic control has little effect on the development and progression of peripheral neuropathy, suggesting that other metabolic syndrome components may contribute to the presence of neuropathy. A parallel phenomenon is observed in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
82
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(98 citation statements)
references
References 47 publications
12
82
2
2
Order By: Relevance
“…We examined the impact of SFA hydrocarbon chain length on mitochondrial trafficking, mitochondrial dysfunction, and apoptosis in sensory DRG neurons based on previous studies suggesting that nerve damage and sensory neuronal dysfunction underlying the progression of DPN is linked to an increased intake of SFAs associated with the Western diet (9,10,17). We found that 24 h treatments with LCSFAs at physiological concentrations of 62.5-250 M palmitate and 31.25-250 M stearate significantly impaired mitochondrial axonal trafficking in a dose-dependent manner, whereas treatments with 31.25-250 M MCSFA laurate and 31.25-250 M LCSFA myristate had no significant impact on mitochondrial movement in DRG axons after 24 h. Moreover, the impairment of mitochondrial trafficking by palmitate and stearate correlated with a reduction in mitochondrial membrane potential and ATP, altered mitochondrial morphology, and an induction of neuronal apoptosis that was not observed in DRG neurons treated with laurate or myristate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined the impact of SFA hydrocarbon chain length on mitochondrial trafficking, mitochondrial dysfunction, and apoptosis in sensory DRG neurons based on previous studies suggesting that nerve damage and sensory neuronal dysfunction underlying the progression of DPN is linked to an increased intake of SFAs associated with the Western diet (9,10,17). We found that 24 h treatments with LCSFAs at physiological concentrations of 62.5-250 M palmitate and 31.25-250 M stearate significantly impaired mitochondrial axonal trafficking in a dose-dependent manner, whereas treatments with 31.25-250 M MCSFA laurate and 31.25-250 M LCSFA myristate had no significant impact on mitochondrial movement in DRG axons after 24 h. Moreover, the impairment of mitochondrial trafficking by palmitate and stearate correlated with a reduction in mitochondrial membrane potential and ATP, altered mitochondrial morphology, and an induction of neuronal apoptosis that was not observed in DRG neurons treated with laurate or myristate.…”
Section: Discussionmentioning
confidence: 99%
“…Saturated fatty acids disrupt mitochondrial trafficking 63 defects associated with T2D, including weight gain, hyperinsulinemia, impaired glucose tolerance, increased HbA1c, and dyslipidemia (10,58). Modeling dyslipidemia in cultures of sensory DRG neurons also induces significant neuronal damage, including oxidative stress, impaired mitochondrial trafficking, dysfunctional axonal mitochondria, bioenergetic reprogramming, and neuronal dysfunction as a result of increased levels of LCSFAs (14-17, 27, 59, 60).…”
Section: Downloaded Frommentioning
confidence: 99%
“…Impaired lipid metabolism and accumulation of oxidized lipids has clearly been implicated in the etiology of diabetic neuropathy . In this study, HDL was increased in the more acute STZ model of diabetes (Table ) but reduced in the more chronic LCR obesity model (Table ).…”
Section: Discussionmentioning
confidence: 53%
“…We expected excitability of Lepr db/db neurons to change with increasing intensity from weeks 10 to 21 as diabetes progressed as diabetic neuropathy is a function of both hyperglycemia and duration in humans (Maser et al 1989; Davies et al 2006), rats (Mattingly and Fischer 1983; Sasaki et al 2002) and mice (Giachetti 1978; Hinder et al 2017; Liu et al 2017). Contrary to this hypothesis, many properties associated with excitability changed in 10-week animals, but were then resolved closer to wild-type levels in the 21-week animals.…”
Section: Discussionmentioning
confidence: 99%